Recovery after domestic, family and sexual violence: impact of a holistic clinical support program on victim-survivors - Davies, Mia; Satyen, Lata; Toumbourou, John W. (Frontiers in Psychology, 2026)
IntroductionRecovery frameworks are crucial to mitigate harm and promote positive outcomes for victim-survivors of domestic, family, and sexual violence (DFSV). Despite this, mental health service system responses are inadequate and there is a lack of specialized support programs to promote recovery and healing.MethodsThis study investigated the impact of a novel, holistic, trauma-and-violence-informed recovery framework (the s-CAPE program) on victim-survivors’ recovery from trauma following DFSV, conducted at a gender-specific, trauma-focused clinical setting in New South Wales, Australia. Qualitative interviews were conducted with 10 victim-survivors who had undertaken the s-CAPE program. Thematic analysis was used to derive themes capturing participants’ experiences and perspectives.ResultsAnalysis yielded seven themes exploring participants’ recovery journey, their experiences at the service, its impact on their functioning, and preferences for care. Participants largely considered the s-CAPE program beneficial for their recovery and experienced benefits across a range of mental and physical health domains. Recommendations for service improvement were identified.DiscussionThere is a crucial need for more gender- specific, trauma-focused mental health services utilizing holistic and trauma-and- violence-informed approaches to recovery support. These programs need to be accessible and available for broader populations, requiring increased investment, policy change, and collaboration at the systemic level.